(untitled) (Филологические заметки, 2021)
Metalepsis and metareference are not new concepts in literary theory, but thanks to the hypermediation of contemporary culture, they have acquired a broader meaning that transcends intertextual relations. Metalepsis originally belongs to rhetoric where it denotes any kind of permutation, yet in the sphere of narratology it is understood as "the use of one word instead of another by transferring the meaning […] a synonym of both metonymy and metaphor" (Genette 2006: 6). From Aristotle who reduced metalepsis to analogy and the gift "to notice well what is similar" (Aristotle 2008: 1459a), by development of media that not only depict but also create reality, we have come to metalepsis as a figure that unites author and work, connects the reader with the narration and by broadening the meaning leads to the metadiegetic breaking down of the boundaries between fiction and reality: "The limits of the use of metalepsis are set only by the recipient’s ability to understand it in the right way. If the author’s intention to go beyond the framework is too confusing, such a figure does not achieve its goal" (Petković 2018: 239). Narratologist Werner Wolf noticed the similarity of metalepsis, thus defined, with the notion of metareference, which establishes intertextual and intermedial connections in the context of reality oversaturated with media content, producing a new phenomenon of transmediality – the influence of form (McLuhan 1971: 41) on the narrative and its communication with recipients: „‘Metareference’ as a transmedial concept can in brief be explained as follows: metareference issues forth from a logically higher ’meta-level’ within a given artefact or performance, and denotes any self-reflexive reference to, or comment on, media-related aspects of the given medial artefact or performance, of a particular medium or the media in general ”(Wolf 2011: c). Dan Sperber attributes to humans a “metarepresentational capacity” that is “no less fundamental than the faculty for language”, and he claims that “[u] nderstanding the character and the role of this [...] capacity might change our view of what it is to be human (Sperber according to Wolf 2009: 2). The narratologist stance that the narrator’s direct address to the reader is also a metareference, like an authorial metalepsis, places Dušan Radović, a Serbian writer and media author, among the most deserving for creating a literary work that is "a great stage presentation and is as such received" (Jovanović 2001: 83). The founder of modern Serbian children’s literature, Radović is an example of an original creator as a "genius who prescribes a rule for art" (Kant 1991: 191). Radović’s radio play How Bad Words Came About is a good example of involving listeners and readers in metareferential recognition and decoding of meaning in metaconsciousness, and then in a liberating emotional reaction that does not question "reality", but indicates the diversity and richness of its media-mediated meanings.